Pediatric psoriasis induced by HLA‐B46‐Cw1 haplotype: A retrospective study of psoriasis onset after hematopoietic stem cell transplantation. Issue 9 (7th May 2021) - Terui, Hitoshi; Yamasaki, Kenshi; Hagiwara‐Takita, Akiko; Shimada‐Omori, Ryoko; Tsuchiyama, Kenichiro; Saito‐Nanjo, Yuka; Rikiishi, Takeshi; Sasahara, Yoji; Aiba, Setsuya
Abstract: Genome‐wide association studies have identified more than 60 susceptibility loci for psoriasis, highlighting the role of genetics in psoriasis development. Although the HLA region is suggested as the most prominent susceptibility locus, the role of the HLA haplotype in the development of psoriasis is unclear. The aim of this study is to investigate how HLA haplotype changes affect the onset of psoriasis and which HLA haplotypes are associated with the development of psoriasis. A longitudinal, retrospective case series study of children was conducted at Tohoku University Hospital in Japan, between November 1981 and October 2020. We evaluated a total of 378 pediatric patients who underwent hematopoietic stem cell transplantation in the Department of Pediatrics. The background of these patients and their HLA haplotypes before and after transplantation was assessed. Among the 378 cases, aged 0–22 years old (median age 6) identified, 117 cases received autologous transplantation, 260 cases received allogeneic transplantation, and one case received syngeneic transplantation. Only two cases developed de novo psoriasis, and these cases had acquired HLA‐B46‐Cw1 after allogeneic transplantation. Others who had HLA‐B46‐Cw1 before and after allogeneic transplantation did not develop psoriasis. Our findings suggest that the HLA‐B46 and HLA‐Cw1 combination contributes to the development of psoriasis in this Asian population.